Learning of Health Care Management during Covid19 from doctor administrators perspective A Viewpoint - Dr. Nilanjana Ghosh; Prof. Dr. J. Ojha; Prof. Dr. A. C. Baishya (Innovative Journal of Medical and Health Sciences, 2023)
Covid-19 pandemic created a multitude of acute challenges for health care delivery systems, including inadequate infrastructure and special logistics, supply shortages, the need for care redesign, and financial loss. Complexity science views health care delivery ystems as complex adaptive systems that operate in highly complex and unpredictable environments. The perspective assumes that much of ystemal life is unknowable, uncertain, or unpredictable and thus cannot be standardized and controlled.A surprise event can be characterized in three dimensions: the complexity of its source, the speed of its spread, and the unpredictability of its scale and impact.1 The Covid-19 pandemic is a powerful reminder that we live in a highly complex and unpredictable world. For health care delivery ystems, systematic responses to the pandemic have required departures from many conventional practices. The Covid-19 pandemic has presented an array of novel and acute challenges, from managing the supply chain for personal protective equipment (PPE) to adjusting workforce infrastructure and special logistics to coping with financial loss. In the midst of these challenges lies an opportunity for health care leaders to better position and transform their ystems for a future of unpredictable surprise.